2019
DOI: 10.3390/ani9121165
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism for Coping Styles Complements Traditional Methods for Sex Determination in a Multivariety Endangered Hen Breed

Abstract: Sex determination is key to designing endangered poultry population conservation and breeding programs when sex distribution departs from Hardy–Weinberg equilibrium. A total of 112 Utrerana chickens (28 per variety, partridge, black, white, and franciscan) were selected for hatching day sexing. Sex assignation was performed through 10 methods. Three sex assignment criteria comprised criteria found in literature, opposite criteria to that in the literature, and composite criteria combining methods reporting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 56 publications
(67 reference statements)
1
12
0
Order By: Relevance
“…This was due to the fact that some animals died, and others were donated to local farms (as part of an Andalusian turkey breed recovery program) before the sexual dimorphism of the individuals became evident. In the literature, it has been reported that samples of around 100 or even fewer individuals report 95% sexing accuracy in other local poultry species ( 5 , 9 , 26 ). Therefore, of the total of 972 observations that were obtained, only 506 observations were used in the analyzed database, of which the individual sex was confirmed and a complete sexing determination procedure of three appraisers was collected.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This was due to the fact that some animals died, and others were donated to local farms (as part of an Andalusian turkey breed recovery program) before the sexual dimorphism of the individuals became evident. In the literature, it has been reported that samples of around 100 or even fewer individuals report 95% sexing accuracy in other local poultry species ( 5 , 9 , 26 ). Therefore, of the total of 972 observations that were obtained, only 506 observations were used in the analyzed database, of which the individual sex was confirmed and a complete sexing determination procedure of three appraisers was collected.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the fact that differences in the reaction to acoustic stimuli between the sexes have been thoroughly studied in chicks (60)(61)(62)(63)(64)(65)(66)(67), the behavior/coping style or "slap" technique has scarcely been reported as a sex discriminant technique. It was only (5) who evaluated its applicability in a chick sex-determining study. In line with these results, the "slap technique" reports significant results supporting its feasible applicability for sex determination in domesticated Meleagris gallopavo which had never been described in turkey species prior to this study.…”
Section: Sourcementioning
confidence: 99%
See 3 more Smart Citations